Kualitas Semen Beku Babi Peranakan Landrace pada Berbagai Level Madu Dalam Pengencer Tris-Kuning Telur - Maria Meldiana Jemamu; Wilmientje Marlene Nalley; Yustiany Yuliana Bette; Thomas Mata Hine (JURNAL KAJIAN VETERINER, 2026)
Information regarding the optimal concentration of honey in Tris-egg yolk extender to maintain the quality of frozen boar semen remains limited. This study aimed to evaluate the effect of honey supplementation on the quality of frozen semen of landrace crossbred boars. Honey was selected due to its antioxidant properties and its role as an energy source (glucose and fructose), which may protect spermatozoa from cryodamage during the freezing process. This experiment applied a completely randomized design with five treatments and four replications. Semen was collected from four landrace crossbred boar aged -2,5 years with ≥75% motility and ≤20% abnormalities. The treatments were T0 (control without honey), T1 (0,75%), T2 (1,50%), T3 (2,25%), T4 (3%) honey in Tris-egg yolk extender. Observed parameters included motility, viability, abnormality and recovery rate after thawing. Statistical analysis showed that honey supplementation significantly affected (P<0,05) semen quality. The best result was obtained at 2,25% honey (T3),with post-thaw motility of 42,35%, viability of 59,80%, abnormality of 10,11%, and recovery rate of 52,64%. It can be concluded that 2,25% honey supplementation in Tris-egg yolk extender is the optimal concentration for maintaining the quality of frozen semen of landrace crossbred boars.